2012
DOI: 10.1073/pnas.1118329109
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic hydrogen evolution from a covalently linked dicobaloxime

Abstract: A dicobaloxime in which monomeric Co(III) units are linked by an octamethylene bis(glyoxime) catalyzes the reduction of protons from p-toluenesulfonic acid as evidenced by electrocatalytic waves at −0.4 V vs. the saturated calomel electrode (SCE) in acetonitrile solutions. Rates of hydrogen evolution were determined from catalytic current peak heights (k app ¼ 1100 AE 70 M −1 s −1 ). Electrochemical experiments reveal no significant enhancement in the rate of H 2 evolution from that of a monomeric analogue: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
99
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 37 publications
(39 reference statements)
3
99
0
2
Order By: Relevance
“…However, they also stated that although simulation of the CV for a monometallic mechanism did not give satisfactory results, this possibility could not be ruled out. The activity comparison of a dicobaloxime and its monomeric analogue by Gray and co‐workers revealed no significant enhancement, which suggests that protonolysis rather than homolysis is responsible for catalysis 38. Therefore, a well‐defined bimetallic HER mechanism has not been recognized and is of great interest and fundamental importance.…”
mentioning
confidence: 99%
“…However, they also stated that although simulation of the CV for a monometallic mechanism did not give satisfactory results, this possibility could not be ruled out. The activity comparison of a dicobaloxime and its monomeric analogue by Gray and co‐workers revealed no significant enhancement, which suggests that protonolysis rather than homolysis is responsible for catalysis 38. Therefore, a well‐defined bimetallic HER mechanism has not been recognized and is of great interest and fundamental importance.…”
mentioning
confidence: 99%
“…Savéant Moreover, electrochemical studies of a covalently linked dicobaloxime revealed that the rate of hydrogen evolution was not signicantly different from that of a monomeric analogue. 96 These experiments suggested that hydrogen evolution likely occurs by protonation of reductively generated Co II -H rather than homolysis of two Co III -H units.…”
mentioning
confidence: 99%
“…However, only marginal improvements over the most basic complexes have been realized. [34][35][36] The two most widely known and cited cobaloxime case studies are those that involve the dimethyl and diphenyl glyoxime ligands (specifically, [Co(dmgBF 2 ) 2 (MeCN) 2 ] and [Co(dpgBF 2 ) 2 (MeCN) 2 ], Fig. 1).…”
Section: Introductionmentioning
confidence: 99%